Small European states and Brexit: Comparing the coping strategies of Portugal and Finland - Raimundo, A.; Ferreira-Pereira, L. C.; Jokela, J. (International Politics, 2025)
Brexit was a major European Union crisis with acute implications for smaller European countries. Both Portugal and Finland have considerably relied on the EU as small, geographically peripheral and ‘core’ member states. The comparison of their strategic responses to Brexit shows significant ‘sheltering’ within the EU but also more pro-active strategies in specific areas. While a hedging of bets was more prominent for Portugal in the foreign policy-area, reacting to the risk of a less ‘Atlantic’ EU, for Finland it was more notorious in the political economy domain where the country lost an important ‘liberal’ ally. These original comparative findings highlight both the EU’s enduring importance for small European states and the national efforts to preserve autonomy and influence under a more volatile continental landscape. The article also advances the ongoing discussion on the strategic adjustment to Brexit by suggesting possible factors helping understanding the pursuance of different coping strategies.